Editorial: VERITAS ET SCIENTIA - Zegarra Alvarado, Noribal J. (2018)
VERITAS ET SCIENTIA, is a publication of the Graduate School of the Private University of Tacna. It is published semiannually since 2012, submitted to editorial arbitration and review of its articles by pairs of distinguished research, academic and professional background. From the VOL. 7 N.- 1, corresponding to June 2018, is also published in Open Journal Systems platform. Open Journal Systems (OJS) is a platform for publishing and managing online magazines that was first launched in 2002, as an open source software freely distributed by Public Knowledge Project (Willinsky, 2005). The software was developed as part of the Public Knowledge Project research program at the University of British Columbia (UBC) in Vancouver, Canada, under the direction of John Willinsky, with the subsequent participation of the University Library Simon Fraser, the Canadian Center for Publication Studies and the Stanford University. OJS was originally programmed by university students at UBC, led by Kevin Jamieson, with a research grant of the Social Sciences Research Council and Humanities of Canada that sought to explore the viability and consequences of helping printed publications to publish their content online. OJS was designed to manage the workflow of the journal, from the presentation of the manuscript, to editorial work, and then publication; while offering a means to publish an online edition and better manage the operating costs of the magazine (Willinsky, 2006). This system was developed within a climate of concern among journal editors and staff about the costs and means of moving from printed to electronic editions, as well as the viability of open access models (by which, authors put articles freely available in online institutional repositories and journals make their content freely accessible to readers.) OJS is just one of a series of open source journal management systems (see Cyzyk & Choudhury, 2008, for a review of comparable systems). It is being used by approximately 5,000 journals, has had 19 update versions since it was first released in 2002, and is now available in 20 languages. In these types of journals, two closely related factors are distinguished. First, open access is vital for your participation in this global circulation of knowledge. Second, the Internet and open source software allow open access to this set of publications, which has reduced the costs of publication and distribution. In Conclusion, Open Journal Systems represents the effect that Open Source tools may have in journal publishing, facilitating the revitalization of peer-reviewed journals published by academics that occur on a global scale and are available universally. It establishes the degree to which the magazines that implement OJS can be considered part of a wider series of experiments of the digital era in academic communication, which includes not only open access but open data, open files, open source software and initiatives of open research instrumentation (Atkins et al., 2003). The commitment of the academic community with this opening of research and scholarships is reflected in the additional work that is required to ensure this level of openness, which often implies new systems for the management of the academic community. Reflects among a growing portion of that community a sense of responsibility and the value of sharing what is learnt. The priority given to this exchange shows one of the intellectual properties of this work, which distinguishes it, we are tempted to conclude, from other forms of intellectual property. Dr.Cs. Noribal J. Zegarra AlvaradoDirector ESPG – UPTEditor